Physiological and proteomic approaches to address the active role of ozone in kiwifruit post-harvest ripening - Minas, Ioannis S.; Tanou, Georgia; Belghazi, Maya; Job, Dominique; Molassiotis, Athanassios; Vasilakakis, Miltiadis; Manganaris, George A. (My University, 2012)
Post-harvest ozone application has recently been shown to inhibit the onset of senescence symptoms on fleshy fruit and vegetables; however, the exact mechanism of action is yet unknown. To characterize the impact of ozone on the post-harvest performance of kiwifruit (Actinidia deliciosa cv. 'Hayward'), fruits were cold stored (0 °C, 95% relative humidity) in a commercial ethylene-free room for 1, 3, or 5 months in the absence (control) or presence of ozone (0.3 μl l -1) and subsequently were allowed to ripen at a higher temperature (20 °C), herein defined as the shelf-life period, for up to 12 days. Ozone blocked ethylene production, delayed ripening, and stimulated antioxidant and anti-radical activities of fruits. Proteomic analysis using 1D-SDS-PAGE and mass spectrometry identified 102 kiwifruit proteins during ripening, which are mainly involved in energy, protein metabolism, defence, and cell structure. Ripening induced protein carbonylation in kiwifruit but this effect was depressed by ozone. A set of candidate kiwifruit proteins that are sensitive to carbonylation was also discovered. Overall, the present data indicate that ozone improved kiwifruit post-harvest behaviour, thus providing a first step towards understanding the active role of this molecule in fruit ripening
Keywords: Antioxidants; Ethylene; Ozone; Proteins; Kiwifruit; Chemistry; Fruit; Genetics; Proteomics; Metabolism; Open access publishing